Supply Chain and Value Addition of Cotton Byproducts in Asia - SHAIKH, A. J.; PATIL, P. G.; SHUKLA, S. K.; MAGESHWARAN, V.; AMBARE, M. G. (Cotton Research Journal, 2021)
Environmental concerns have stimulated researches in the exploitation of renewable resources in recent years. Such researches make better economic sense when they relate to utilization of waste materials like cotton by-produce. With its vast area under cotton cultivation, India is undoubtedly the largest producer of cotton stalk among world countries and stands to benefit immensely from commercial exploitation of this putative agrowaste. Profiled in this paper is CIRCOT's saga of R & D efforts that have revealed the economic potential of cotton plant by-produce abundant in many Afro-Asian countries.